Current challenges and opportunities in computation and simulation to align 4iR paradigm shift - Shashi Kant Dargar; Viranjay M. Srivastava (IAES Indonesian Section, 2020)
With the advent of 4th Industrial Revolution (4iR or Industry 4.0), the current industry sector is highly automated to increased productivity, flexibility, and quality of products & services. The technology, machinery, materials, inputs, and approaches are radically transforming in the traditional manufacturing companies using several enabling technologies, tools, and systems in this digitization era. Industry 4.0 is the game changer to the end of the conventional applications where computation and simulation play a pivotal role in forecasting and evaluating methodically intractable systems' performance. In this paper, the authors describe the prominence of computation and simulation technology in this industrial transformation and analyze the current challenges and opportunities of computational simulation technologies and tools to uphold the effectiveness.